Endophytes and Epiphytes From the Grapevine Leaf Microbiome as Potential Biocontrol Agents Against Phytopathogens - Bruisson, Sébastien; Zufferey, Mónica; L’Haridon, Floriane; Trutmann, Eva; Anand, Abhishek; Dutartre, Agnès; De Vrieze, Mout; Weisskopf, Laure (Frontiers in Microbiology, 2019)
Plants harbor diverse microbial communities that colonize both below-ground and above-ground organs. Some bacterial members of these rhizosphere and phyllosphere microbial communities have been shown to contribute to plant defenses against pathogens. In this study, we characterize the pathogen-inhibiting potential of 78 bacterial isolates retrieved from endophytic and epiphytic communities living in the leaves of three grapevine cultivars. We selected two economically relevant pathogens, the fungus Botrytis cinerea causing grey mold and the oomycete Phytophthora infestans, which we used as a surrogate for Plasmopara viticola causing downy mildew. Our results showed that epiphytic isolates were phylogenetically more diverse than endophytic isolates, the latter mostly consisting of Bacillus and Staphylococcus strains, but that mycelial inhibition of both pathogens through bacterial diffusible metabolites was more widespread among endophytes than among epiphytes. Six closely related Bacillus strains induced strong inhibition (>60%) of Botrytis cinerea mycelial growth. Among these, five led to significant perturbation in spore germination, ranging from full inhibition to reduction in germination rate and germ tube length. Different types of spore developmental anomalies were observed for different strains, suggesting multiple active compounds with different modes of action on this pathogen. Compared with B. cinerea, the oomycete P. infestans was inhibited in its mycelial growth by a higher number and more diverse group of isolates, including many Bacillus but also Variovorax, Pantoea, Staphylococcus, Herbaspirillum or Sphingomonas strains. Beyond mycelial growth, both zoospore and sporangia germination were strongly perturbed upon exposure to cells or cell-free filtrates of selected isolates. Moreover, three strains (all epiphytes) inhibited the pathogen’s growth via the emission of volatile compounds. The comparison of the volatile profiles of two of these active strains with those of two phylogenetically closely related, inactive strains led to the identification of molecules possibly involved in the observed volatile-mediated pathogen growth inhibition, including trimethylpyrazine, dihydrochalcone, and L-dihydroxanthurenic acid. This work demonstrates that grapevine leaves are a rich source of bacterial antagonists with strong inhibition potential against two pathogens of high economical relevance. It further suggests that combining diffusible metabolite-secreting endophytes with volatile-emitting epiphytes might be a promising multi-layer strategy for biological control of above-ground pathogens.